A Comparative Study of Ring VCO and LC-VCO: Design, Performance Analysis, and Future Trends - N. R. Sivaraaj; K. K. Abdul Majeed (IEEE Access, 2023)
Voltage-controlled Oscillator (VCO) is a prominent part that has been used to generate a stable frequency for the high-frequency transceiver system. This survey encompasses a comparative analysis of two commonly used VCO architectures: the Ring VCO and LC-VCO. The Ring VCO has been constructed with the collection of ring delay cells. Moreover, the LC-VCO utilizes inductors, capacitors, fine-tuning circuits, coarse-tuning circuits to generate frequency. Furthermore, this study investigates an in-depth exploration of VCO structures, operational principles, advantages, limitations, and performance metrics. In addition, it evaluates performance parameters, including operating frequency range, phase noise, figure of merit, and tuning techniques. This research suggests that based on the application and its requirements, the VCO performance parameters need to be varied. This survey employs diverse types of VCO, and its design methods. Implications for future research and study of VCO design and integration are discussed.